Paratesticular papillary serous cystadenocarcinoma: A rare entity in Indian population - Vikram Narang; Neena Sood; Bhavna Garg; Baldev Singh Aulakh (Wolters Kluwer Medknow Publications, 2014)
Ovarian-type surface epithelial carcinomas of testis and paratestis are very rare. These tumors develop from mesothelial inclusions or abnormalities in the development of coelomic epithelium. The diagnosis of these lesions can be difficult, both clinically and radiologically, as morphological, immunohistochemical and ultrastructural features overlap with serous tumors arising in the female genital tract. The pathologist should be aware of the histopathological features and immunostains which help in reaching definite diagnosis. To the best of our knowledge only one such case has been reported in Indian literature. We hereby report a case of young male with this unusual lesion diagnosed on histopathology.